2017
DOI: 10.1371/journal.pone.0182863
|View full text |Cite
|
Sign up to set email alerts
|

Infection-stage adjusted dose of beta-lactams for parsimonious and efficient antibiotic treatments: A Pasteurella multocida experimental pneumonia in mice

Abstract: In this study, the impact of infection stage on clinically and microbiologically efficacious doses and on antibiotic consumption was assessed during a naturally evolving infectious disease, using an original mouse model of pulmonary infection produced by air-borne contamination. When Pasteurella multocida was administered as pathogenic agent to immunocompetent mice, 60% of the animals exhibited clinical symptoms of pneumonia 2 to 4 days after bacterial contamination of the lungs. Two beta-lactam antibiotics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…For example, small differences in the growth rate between resistant mutants and wild type parasites can reduce genetic diversity over time [46]. The few in vivo tests of which we are aware [38,39,[47][48][49][50] involved early or late drug treatment or infections initiated with small or large inocula [39,49]. In these binary cases, resistance typically emerged less readily if infections were treated early or had fewer pathogens to begin with, consistent with the idea that larger populations are more likely to contain resistant mutants.…”
Section: Introductionmentioning
confidence: 69%
“…For example, small differences in the growth rate between resistant mutants and wild type parasites can reduce genetic diversity over time [46]. The few in vivo tests of which we are aware [38,39,[47][48][49][50] involved early or late drug treatment or infections initiated with small or large inocula [39,49]. In these binary cases, resistance typically emerged less readily if infections were treated early or had fewer pathogens to begin with, consistent with the idea that larger populations are more likely to contain resistant mutants.…”
Section: Introductionmentioning
confidence: 69%
“…It has been shown that metaphylactic treatments are associated with higher cure rates than curative treatments administered when animals are already exhibiting clinical signs of disease. 2,3 However, the European guidelines for the prudent use of antimicrobials in veterinary medicine 4 highlight treatment via feed and drinking water as a major concern in the development of antimicrobial resistance.…”
mentioning
confidence: 99%
“…When the delay between onset of bacteriological challenge and AMD treatment is reduced, the concentration–effect relationship is shifted to the left; drug potency is then increased with the lower bacterial load. This has been established both in rodent models (Ferran et al., 2011; Vasseur et al., 2014, 2017) and in target species studies such as the calf model of bacterial infection (Lhermie et al., 2016). Thus, lower AMD doses can be clinically more efficacious in the pre‐patent phase of infection than subsequently, when animals display clinical signs.…”
Section: Pk/pd Target Values For Purpose and Context In Veterinary Mementioning
confidence: 99%